The Effect of Customer Satisfaction and Loyalty on the Financial Performance of PT Perusahaan Listrik Negara (PLN): The Role of Digital Service Systems as a Moderating Variable - Nadiah Zulfi Syafira; Renny Maisyarah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effects of customer satisfaction and customer loyalty on the financial performance of PT PLN (Persero) with digital service systems serving as a moderating variable. Digital transformation in public services has become a critical factor in maintaining organizational competitiveness, especially in meeting evolving customer expectations for accessible and efficient services. Data were collected through surveys of PLN customers and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that customer satisfaction has a positive and significant effect on financial performance, while customer loyalty has a highly significant and strong positive effect. Digital service systems also contribute significantly to financial performance and strengthen the influence of both customer satisfaction and customer loyalty on financial outcomes. The model’s R-Square value of 0.872 indicates a very strong explanatory power. These findings highlight the important role of digital service systems in enhancing the relationship between customer experience and financial performance. The practical implication of this study emphasizes the need for integrated digital service development to improve customer satisfaction and loyalty, thereby supporting sustainable financial performance.